The effect of using different types of solvents towards quality of Azadirachta Indica crude extract / Irham Mohd Saupi - Mohd Saupi, Irham (2023)
Azadiractha indica is one of the greatest herbs and contains several bioactive compounds which are believed to possess several therapeutic properties such as antibacterial, antimicrobial and anti-inflammatory disease. These bioactive compounds can be obtained by using an optimum and appropriate extraction parameter. The extraction parameters include suitable drying methods, suitable solvents to extract polar or non-polar compounds, types of extraction technique and others. However, the comparative scientific study on the effect of using different extraction parameter towards the extraction yield and amount of extracted bioactive compound has been very limited. Therefore, this study aimed to determine the effect of using different types of extraction parameters focusing on different types of solvents towards the extraction yield and amount of extracted bioactive compound. The extraction process was implemented by using maceration technique by using aqueous, methanol, and ethanol as solvents. Then, the concentration of Gallic acid was determined by using High- Performance Liquid Chromatography (HPLC). The findings revealed that the highest extraction yield was shown by the extract from methanol with the value of 15.79%. While Gallic acid was present in every extract and that the highest amount of Gallic acid shown by the extract from Aqueous with the value of 44.70ppm. This finding showed that extraction efficiency varied depending on the solvent utilized.. This study highlights that Azadirachta Indica or neem leaves are one of the useful plants that contain Gallic Acid and it could be optimum extracted by using aqueous.